Employing Nearpod as a Resource to Encourage Active Students in BYOD Mathematics Learning Model - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Amri, Khofifatul (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
In the period of the last few decades, more complex technology have been integrated into our daily lives. Therefore, teachers are advocating that students BYOD (bring your own device). This aims are investigated the activities of students during the lesson, which enables teachers to evaluate their students' progress in learning. In addition to this, students' learning experiences and raise their levels of satisfaction with their education with Nearpod and the dynamic interaction that occurs between them. Descriptive statistics were used for the analysis. Descriptive data for the questions and items were compiled in Excel, and included frequency, percentage, mean, and standard deviation. The goal of this research is to explore how female students feel about using Nearpod in conjunction with a video-conferencing learning system on a Bring Your Own Device (BYOD) learning platform. This study was conducted at Universitas Muhammadiyah Purwokerto (n = 78 students) and Purwokerto Secondary School in Central Java (n = 83 students and 9 teachers), during the even semester of the 2020/2021 school year. The objectives of this study required the development and administration of a questionnaire to all of the women enrolled in the "Mathematics Education" course. Researchers concluded from their study that students are open to using their own devices in class and are willing to benefit from the affordances provided by the BYOD platform and the Nearpod to engage in active learning during lectures. Therefore, there has to be more work done by universities to figure out which of the growing elements of education should be prioritized in order to create the best possible conditions for instruction and learning.